ENHANCING THE OPERATIONAL EFFICIENCY OF DIRECT CURRENT DRIVE BASED ON USE OF SUPERCONDENSER POWER STORAGE UNITS - Mukha А. M.; Kostin М. О.; Kurylenko О. Y.; Tsyplia, H. V. (Science and Transport Progress, 2017)
Purpose.The scientific work is intended to analyse the expansion of the load range and the implementation of regeneration braking (RB) of the direct current drive by using the supercondenser power storage units. Methodology.To solve the problem, we use the methods of the electric drive theory, impulse electronics and the method of calculation of transient electromagnetic processes in linear electric circuits in the presence of super-condensers therein. Findings.The stiffness of the mechanical and electromechanical characteristics of a series motor is significantly increased, which makes it possible to use a DC drive under load, much smaller than 15…20% of the nominal one. Numerical calculations of the operation process of the supercondenser power storage unit were fulfilled with a sharp decrease in the load of a traction electric motor of a direct current electric locomotive. The possibility of RB of the direct current drive with the series motor is substantiated. The equations of the process of charging and discharging of super-condenser storage unit in RB mode are solved. The authors examined the effect of capacitance on the nature of maintaining the excitation current of an electric motor in the mode of small loads.Originality.The paper developed theoretical approaches for the transformation of soft (mechanical and electromechanical) characteristics into hard ones of DC series motors. For the first time a new, combined method of the series motor RB is proposed and substantiated. Further development obtained the methods for evaluating the storage unit parameters, taking into account the criteria for reliable parallel operation of super-condensers with an electric motor field. Practical value.The proposed and substantiated transformation of soft characteristics into stiff ones allows us to use general-purpose electric drives with series motors and at low loads, and in traction electric drives - to reduce the intensity of electric stockwheel slipping. Thedevelopedmethodofsolvingtransitionalequationsmakesitpossibletotakeintoaccounttherandomnatureofthevoltagechangeonthemotorinsuper-condenserdrivechargeanddischargemodes. The proposed combined method makes it possible to carry out RB at low speeds of the motor armature as well, and thus to increase energy efficiency of operation of electric drives of this type.